Impact of Educational Intervention on Pharmacovigilance Knowledge, Attitude, and ADR Reporting among Pharmacy Students: An Interventional Study - Thomas, Lijo Joseph; Parakadavil, Athira; K, Fathimath Nidha; Rahana, Rahana; L, Lal Prasanth M (Indian Journal of Pharmacy Practice, 2026)
Aim: To assess the awareness and identify barriers related to pharmacovigilance and ADR reporting among healthcare students, and to evaluate the impact of an educational intervention. Materials and Methods: A prospective pre-post interventional study was conducted among 149 pharmacy students at Dr. Moopen’s College of Pharmacy, Wayanad, over six months. A validated, structured questionnaire assessing knowledge, attitude, awareness, and perceived barriers was administered before and after a 30-min educational session on pharmacovigilance and ADR reporting. Data were analyzed using SPSS, with statistical significance set at p < 0.05 using pairedt-test and Wilcoxon signed-rank test. Results: A total of 149 students completed the study. Baseline findings showed moderate knowledge and awareness of pharmacovigilance, with notable gaps in ADR reporting procedures. Post-intervention, there was a statistically significant improvement in knowledge scores (mean increased from 7.77 ± 1.77 to 10.01 ± 0.39; p < 0.001). Awareness of pharmacovigilance systems, including PVPI and ADR reporting processes, improved to 100%. Students’ willingness to report ADRs increased from 89.3% to 98.7%. Recognition of reporting barriers also improved significantly. No significant differences were observed in baseline knowledge based on gender or course of study. Conclusion: The educational intervention was highly effective in enhancing pharmacovigilance knowledge, awareness, and attitudes among pharmacy students. Integrating structured pharmacovigilance training into academic curricula can reduce reporting barriers and promote active participation in ADR reporting, ultimately contributing to improved patient safety.
Keywords: Adverse Drug Reaction (ADR); Awareness; Educational Intervention; Knowledge; Pharmacovigilance; Pharmacy Students; Reporting Barriers